2015
DOI: 10.1039/c4fo00621f
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo digestion of carp muscle tissue – ACE inhibitory and antioxidant activities of the obtained hydrolysates

Abstract: In the digestive tract of humans, bioactive peptides, i.e. protein fragments impacting the physiological activity of the body, may be released during the digestion of food proteins, including those of fish. The aim of the study was to establish the method of human ex vivo digestion of carp muscle tissue and evaluate the angiotensin I-converting enzyme inhibitory and antioxidant activities of hydrolysates obtained after digestion. It was found that the hydrolysates of carp muscle tissue obtained with the three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…New and intensive band was detected for the myofibrillar protein chains with MW $ 35 kDa. A similar result was observed in a previous study on the hydrolysis of carp muscle tissue (Borawska et al, 2015) and salmon myofibrillar proteins (Darewicz et al, 2014).…”
Section: Sds-page and Protein Content Of Hydrolysatessupporting
confidence: 88%
See 1 more Smart Citation
“…New and intensive band was detected for the myofibrillar protein chains with MW $ 35 kDa. A similar result was observed in a previous study on the hydrolysis of carp muscle tissue (Borawska et al, 2015) and salmon myofibrillar proteins (Darewicz et al, 2014).…”
Section: Sds-page and Protein Content Of Hydrolysatessupporting
confidence: 88%
“…The ex vivo hydrolysis was carried out according to Borawska, Darewicz, Vegarud, Iwaniak, and Minkiewicz (2015). Gastric (HGJ) and duodenal (HDJ) juices were obtained from 6 volunteers as previously described (Ulleberg et al, 2011).…”
Section: Ex Vivo Hydrolysismentioning
confidence: 99%
“…Simulation of human digestion was carried out according to Borawska et al Gastric (HGJ) and duodenal (HDJ) juices were collected from six healthy volunteers according to Ulleberg et al The aspiration was approved by the Norwegian Ethical Committee, and all volunteers had given written consent to participate in the study. Pepsin activity of HGJ was 36.85 U mL −1 , and the total proteolytic activity of HDJ was 12.35 U mL −1 assayed according to Ulleberg et al …”
Section: Methodsmentioning
confidence: 99%
“…A number of digestion models and methods have been suggested and designed to this end. The best way to simulate human enzymatic digestion and physiological conditions is to aspirate gastrointestinal juices from human volunteers to be used in the ex vivo digestion method …”
Section: Introductionmentioning
confidence: 99%
“…Results showed that GI digestion in general increased their antioxidant properties measured by diff erent in vitro assays. In contrast, Borawska et al (28) showed that high degree of hydrolysis of carp muscle tissue led to products with lower free radical scavenging activity. *analytical variation of the amino acid analyses ranged from 6 to 11 %, N=1; HAA=hydrophobic amino acids (alanine, valine, isoleucine, leucine, tyrosine, phenylalanine, proline, methionine and cysteine), PCAA= positively charged amino acids (arginine, histidine and lysine), NCAA=negatively charged amino acids (aspartic+asparagine, glutamic+glutamine, threonine and serine), AAA=aromatic amino acids (phenylalanine and tyrosine), SAA=sulfur-containing amino acids (methionine and cysteine)…”
Section: Antioxidant Activity In the Cells And Cellular Metabolic Energymentioning
confidence: 99%